Removal of artificial anionic dye by electrocoagulation and electro-oxidation combined system using aluminum and nano (Cu-Mn-Ni) composite electrodes - Jasim, Reman A.; Salman, Rasha H.; Zabar, Muhannad K. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The combined system of electrocoagulation (EC) and electro-oxidation (EO) is one of the most promising methods in dye removal. In this work, a solution of 200 mg/l of Congo red was used to examine the removal of anionic dye using an EC-EO system with three stainless steel electrodes as the auxiliary electrodes and an aluminum electrode as anode for the EC process, Cu-Mn-Ni Nanocomposite as anode for the EO process. This composite oxide was simultaneously synthesized by anodic and cathodic deposition of Cu (NO3)2, MnCl2, and Ni (NO3)2 salts with 0.075 M as concentrations of each salt with a fixed molar ratio (1:1:1) at a constant current density of 25 mA/cm2. The characteristics structure and surface morphology of the deposited nano oxides onto the graphite substrates were determined by (XRD), (FE-SEM), (AFM), and (EDX). The results shown that nano Cu-Mn-Ni oxides were successfully deposited onto the anode and cathode. The crystal size and root mean square for the cathode were 30.79 nm and 79.36 nm, respectively, while for the anode, they were 24.19 nm and 41.88 nm, respectively. Furthermore, the combined system was examined for C.D, NaCl concentration, and time. In the EC-EO combined system, the cathode and anode were efficient when used as anodes for the EO process, besides aluminum. The cathode was more effective in the removal process than the anode due to its larger crystal size and the rough, granular shape of its surface. When current density (C.D) increased from 3 to 6 mA/cm², the removal efficiency shifted from 95% to 98%. However, excellent removal of 98% and 96.5% was attained with 1.665 and 2.0859 kWh/kg of dye as energy consumption in the presence and absence of NaCl salt, respectively by applying 6 mA/cm2 within 20 min of electrolysis.